2022
DOI: 10.3390/app121910129
|View full text |Cite
|
Sign up to set email alerts
|

Healthier Meat Products Are Fashionable—Consumers Love Fashion

Abstract: Meat manufacturers are nowadays in a very unenviable position. Both meat and meat products require the utilization of various additives due to their chemical composition. On the other hand, consumers demand fresh, additive-free, and high-quality products with extended shelf-life, which might be considered as healthier, even functional food. These facts push manufacturers and researchers in pursuit of modern technologies and supplements to meet these high demands. Since a high daily intake of sodium and fat mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 186 publications
0
9
0
Order By: Relevance
“…It is essential for technological and sensory properties, shelf-life and safety of meat products. Its influence depends on salt content, form of meat (whole muscle/ground), processing procedures (heating, drying, mixing/grinding) and can be summarized as: extraction and activation of myofibrillar proteins, meat emulsion formulation and stabilization, improvement of the water-holding capacity (WHC) and defining flavour (Kurćubić et al, 2022). High sodium intake has been corre-lated with high blood pressure, while salt is the major source of sodium in meat products, in which it accounts for approximately 79% of the sodium (Desmond, 2006).…”
Section: Reduction Of Salt (Sodium)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential for technological and sensory properties, shelf-life and safety of meat products. Its influence depends on salt content, form of meat (whole muscle/ground), processing procedures (heating, drying, mixing/grinding) and can be summarized as: extraction and activation of myofibrillar proteins, meat emulsion formulation and stabilization, improvement of the water-holding capacity (WHC) and defining flavour (Kurćubić et al, 2022). High sodium intake has been corre-lated with high blood pressure, while salt is the major source of sodium in meat products, in which it accounts for approximately 79% of the sodium (Desmond, 2006).…”
Section: Reduction Of Salt (Sodium)mentioning
confidence: 99%
“…Moreover, meat is almost an exclusive source of several bioactive compounds with antioxidative, anti-inflammatory, anti-carcinogenic and anti-atherosclerotic properties, such as conjugated linoleic acids, carnosine, anserine and taurine (Pereira & Vicente, 2013;Young et al, 2013). Since meat as essential food needed to be preserved, ancient people developed meat products by combining different animal tissues with salt and spices, and applying early preservation techniques -drying, heating and smoking (Kurćubić et al, 2022). For centuries, these products have been an excellent source of protein, energy and other nutri-ents.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that consumers' concerns about food quality have been increasing, in recent decades, particularly concerning the perceived healthiness of Molecules 2023, 28, 3332 2 of 14 food [1][2][3]. Meat and various meat products are important sources of high-quality proteins, fats, and minerals as essential nutrients [4,5]. As animal welfare concerns grow and consumers become more conscious of food quality, there is an increasing focus on improving the quality, safety, and nutritional value of meat.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of HS may vary in severity and duration, the exposure of animals to elevated temperatures increases the concentration of omega-6 fatty acids in muscle [6,11]. However, the effects of HS on meat quality across animal species and breeds are inconsistent and are likely due to differences in heat resistance [4,20]. These impacts on carcass characteristics have been reported in many species, and HS has been well known to reduce feed intake and carcass yield in poultry [13,21], pigs [22], goats [23], cattle [24], and lambs [25].…”
Section: Introductionmentioning
confidence: 99%
“…The rising interest in sodium-reduced meat products, as well as clean label meat products containing natural compounds instead of additives, have brought the possibility of applying new strategies for this challenge, resulting in the presence of innovative and reformulated products in the market [ 9 ]. Among these strategies, the use of powdered plant raw materials and extracts (able to provide a salty flavor, along with additives that can offer similar technological traits from NaCl) have been suggested [ 10 , 11 , 12 ]. The reformulation (including the use of ingredients from algae and plant origin) appears to have a huge potential, although it is necessary to take into consideration their effect in products color, flavor, and others key aspects.…”
Section: Introductionmentioning
confidence: 99%